ANALISA KEANDALAN FISIK BANGUNAN GEDUNG ASRAMA PUTRA KABUPATEN NATUNA KOTA PONTIANAK - Yason, Andronikus Octa; Amsal, Panji Gemilang; Nernawani, Nernawani; Moambura, Ayub Konstatinus (Jurusan Teknik Sipil Polnep, 2020)
This study aims to determine the reliability of the building of the Male Dormitory in Natuna Regency in Pontianak City, seeing the current condition of the building, it has some damage to the building, such as paint that has started to peel off on the front, sides and back of the building, the ceiling is seeping, the walls are starting to crack in some parts of the building. By looking at the current condition of the Natuna Regency Male Dormitory Building, it is necessary to conduct research to determine whether the building is still reliable or not based on the Building Technical Requirements as stated in Law Number 28 of 2002 concerning Buildings. The purpose of this study is to analyze the architectural reliability of a building, can analyze the reliability of the structure of a building and can analyze the reliability of the utility of a building. The research was conducted by using data collection methods. Data obtained by using two types of data collection, namely primary data containing survey results and primary data containing the literature used. The results of this study indicate that the architectural reliability of the Male Natuna Dormitory Building is 85.63% where this value is considered less reliable because it is in the 75 - 90% range based on the provisions of the Residential Building Research Center, the reliability of the structure in the Male Natuna Dormitory Building is 100% where this value is considered reliable because it is in the 95 - 100% range based on the provisions of the Residential Building Research Center, reliability of utility in the Male Natuna Dormitory Building is 55.42% where this value is considered an unreliable condition because it is <95% based on the provisions of the Residential Building Research Center.